Relationship between socioeconomic risk factors, psychological inflexibility, and depression among individuals living in rural areas - Yee Hsuen Cheng; Walton Wider; Mohd Hamizie Tahir; Nicholas Tze Ping Pang; Sharon Sharmini R. Mohan; Vie Cheong Thong; Ming Gui Tan; Norhayati Adnan; Joanne Justin (Universiti Putra Malaysia, 2024)
Introduction: A high prevalence of depression in rural areas has led to increases in suicidality. Our study aim is to investigate the role of psychological inflexibility as a mediator in the relationship between socioeconomic risk factors and depression in a rural population in Borneo. Methods: 115 participants were enlisted in this cross-sectional study that utilized convenience sampling of all participants in a community healthcare program. Three questionnaires were used: the sociodemographic risk factor questionnaire, the PHQ-9 questionnaire to measure depression, and the AAQ-II questionnaire to measure psychological inflexibility. The sociodemographic data was analyzed and described using descriptive statistics using IBM SPSS version 28.0. The statistical analysis of the mediating model was carried out using PLS-SEM and SmartPLS 4.0 (Henseler et al., 2016). An indirect effects analysis was performed on the structural model to explain the mediating effect of psychological inflexibility between socioeconomic factors and depression. Results: The analysis showed that psychological inflexibility acts as a mediator in the relationship between both being married and native, and depression. Other socioeconomic risk factors such as gender, employment, and education level did not mediate between psychological inflexibility and depression. Conclusion: Marriage and native ethnicity are identified as a buffer and protective factor from psychological inflexibility and depression. Future research should focus on establishing a clearer picture of how marital status and native ethnicity of Sabah affects psychological flexibility and mental health.